1994
DOI: 10.1016/0014-5793(94)00810-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and hypotensive activity of proadrenomedullin N‐terminal 20 peptide (PAMP)

Abstract: Proadrenomedullin N-terminal 20 peptide (PAMP) is a candidate for a novel biologically active peptide processed from an adrenomedullin precursor. Using a radioimmunoassay for human PAMP, major and minor immunoreactive PAMPs were purified from porcine adrenal medulla and complete amino acid sequences were determined. The major immunoreactive peptide was PAMP itself with an amidated carboxy terminus. The minor one was determined to be PAMP[5-201. An intravenous bolus injection of human PAMP in anesthetized rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 6 publications
3
82
1
Order By: Relevance
“…Since the previous RIA for the entire PAMP-20 molecule showed only 19% cross-reactivity with PAMP-12 [6], the existence of PAMP-12 in vivo was not identified in previous studies [7,8]. In the present study, the immunoreactive peak of PAMP-12 was demonstrated to be reproducibly higher than that of PAMP-20 by the RP-HPLC analyses, indicating that this peptide exists in vivo as an endogenous peptide.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Since the previous RIA for the entire PAMP-20 molecule showed only 19% cross-reactivity with PAMP-12 [6], the existence of PAMP-12 in vivo was not identified in previous studies [7,8]. In the present study, the immunoreactive peak of PAMP-12 was demonstrated to be reproducibly higher than that of PAMP-20 by the RP-HPLC analyses, indicating that this peptide exists in vivo as an endogenous peptide.…”
Section: Discussioncontrasting
confidence: 61%
“…With the use of this RIA, the existence of PAMP-20 in vivo was demonstrated by the isolation and characterization of the peptide from both human pheochromocytoma and porcine adrenal medulla [7,8]. PAMP-20 elicited a potent hypotensive effect when injected intravenously in anesthetized rats [8]. PAMP-20 also inhibited carbachol-induced catecholamine synthesis and secretion in cultured bovine adrenal medullary cells [9,10].…”
Section: *Corresponding Author Fax: (81) (985) 85-6596mentioning
confidence: 99%
“…9,10 PAMP, but not AM, was specifically expressed by some NE cells of the human normal prostate. 11 NE expression in other tissues has also been associated with PAMP production.…”
mentioning
confidence: 93%
“…12 However, this peptide was first described in the vascular wall and in endocrine organs in normal and pathologic situations. 13 PAMP is a pluripotent peptide initially identified as a vasodilator, 9 but it can additionally act as a neural transmission inhibitor, 14 an endocrine secretion inhibitor 15 or a cell growth suppressor. 16 Some of these roles could contribute to the regulation of prostatic homeostasis or functioning.…”
mentioning
confidence: 99%
“…ADM inhibits ACTH secretion from the pituitary, insulin secretion from the pancreas, and catecholamine secretion from the adrenal gland [28]. PAMP is biologically active and it is a hypotensive agent [4,15] that decreases catecholamine secretion [13,29,36].…”
Section: Introductionmentioning
confidence: 99%